2010
DOI: 10.1055/s-0030-1249831
|View full text |Cite
|
Sign up to set email alerts
|

“Anaortic” Off-Pump Coronary Artery Bypass Grafting Significantly Reduces Neurological Complications Compared to Off-Pump and Conventional On-Pump Surgery with Aortic Manipulation

Abstract: In this series "anaortic" OPCAB surgery significantly decreases the risk of neurological complications compared to both ONCAB and OPCAB with aortic manipulation. If possible, we advocate avoiding aortic manipulation in OPCAB surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 26 publications
1
11
0
Order By: Relevance
“…Baseline characteristics of included studies, patient demographics, number of distal anastomoses, and PADs used are listed in Table 1. A total of 18 studies [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] (among them 3 RCTs 24,26,27 ) comprising 25 163 patients met the inclusion criteria and entered the final analysis. Patients were divided into 3 groups: (1) aortic "no-touch"-8291 patients; (2) PAD -3192 patients; and (3) side-clamp OPCAB-13 680 patients, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Baseline characteristics of included studies, patient demographics, number of distal anastomoses, and PADs used are listed in Table 1. A total of 18 studies [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] (among them 3 RCTs 24,26,27 ) comprising 25 163 patients met the inclusion criteria and entered the final analysis. Patients were divided into 3 groups: (1) aortic "no-touch"-8291 patients; (2) PAD -3192 patients; and (3) side-clamp OPCAB-13 680 patients, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, published data suggested that the avoidance of aortic manipulation is the most important factor in reducing the risk of neurological complications (84,85). Patients with extensive disease of the ascending aorta pose a special challenge for on-pump CABG; for these patients, cannulation or cross-clamping of the aorta may create an unacceptably high risk of stroke.…”
Section: Off-pump Cabg Versus Traditional On-pump Cabgmentioning
confidence: 99%
“…Of course, coronary revascularization using an aortic no-touch technique has yielded excellent clinical outcomes. 13,14 In addition, total arterial coronary revascularization has been performed with good results. 15,16 However, we believe that only one technique cannot be applied to all candidates, and our technique could be carefully considered in select patients on a case-by-case basis.…”
Section: Discussionmentioning
confidence: 99%